2021
DOI: 10.1080/02640414.2021.1903685
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the minimum visual disability criteria for Para nordic and Para alpine skiing using simulated vision impairments

Abstract: The International Paralympic Committee Classification Code requires sports to develop evidence-based, sports-specific classification systems. This project aimed to determine the minimum eligibility criteria for Para nordic and Para alpine skiing by simulating vision impairments and measuring the impact of the impairments on performance in twenty-two nordic (28.09 ± 9.68 years; 16 male) and eleven alpine (37.91 ± 18.9 years, 11 male) able-sighted skiers. Eight visual acuity (VA)/contrast sensitivity (CS) (Cambr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…To achieve fair inclusion criteria, it is necessary to identify at what level VI starts to affect performance. Such studies have been undertaken for other VI sports such as shooting, Nordic and alpine skiing 7,10,11 . While there has been work that identified 10 D of defocus can impact putting, 29,30 further research is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve fair inclusion criteria, it is necessary to identify at what level VI starts to affect performance. Such studies have been undertaken for other VI sports such as shooting, Nordic and alpine skiing 7,10,11 . While there has been work that identified 10 D of defocus can impact putting, 29,30 further research is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…New classification systems not adhering to this model are being trialled for shooting and are underdevelopment for football, skiing, athletics and swimming. [6][7][8][9][10][11] Other sports such as VI golf are currently not eligible as a Paralympic sport, partly due to the lack of an evidence-based classification procedure.…”
mentioning
confidence: 99%
“…However, this approach is less suitable for in-situ tasks such as judo that rely on the functional co-adaptation between two competing athletes (Krabben, Orth et al, 2019). Other approaches that could be used in-situ either use (e.g., spectacle) lenses where the simulated visual field loss does not move with the eyes, (e.g., Stalin & Dalton, 2021) or use conventional contact lenses that are unable to simulate precise field losses. Recent advances in augmented reality may offer a promising means of simulating visual field loss while performing in-situ tasks (Jones et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research in VI rifle shooting demonstrated that only one class was necessary in that sport, because functionally blind athletes could perform just as well as athletes with much less impairment, presumably because in that sport they can effectively rely on the auditory feedback used in the sport to guide the rifle [ 8 – 13 ]. Research has also begun in other VI sports including football [ 14 , 15 ], judo [ 16 21 ], skiing [ 22 , 23 ], athletics [ 24 ], goalball [ 25 ], and swimming [ 7 ].…”
Section: Introductionmentioning
confidence: 99%